Exploration of Common Theme of Post-colonial Perspectives in Colonial Literature - Paudel, Yog Raj (Kaumodaki: Journal of Multidisciplinary Studies, 2026)
Post-colonialism as a literary theory deals with literature produced in response to the experiences both the colonizers and the colonized had during colonization and after decolonization. With an inductive reasoning approach on various primary and secondary data about colonialism, neocolonialism, and cultural resistance, this article presents representative responses of critics who shaped the post-colonial theoretical framework in post-colonial literary discourse. It particularly discusses what post-colonial theory as literary criticism focuses its debates on, how culture, language, and other features are taken as one’s identities, and why cultural hegemony over the colonized becomes a matter of responses and resistance. From various critical perspectives and analyses of theorists, this article concludes that orientalism as well as other Western discourses about the natives and culture of colonized land in any place, is just the Western style for dominating the colonized, reconstructing ideology, influencing the culture, and having authority over them. This paper recommends that colonized people must adopt counter cultural resistance approach through writing back to reject colonial view like ‘oriental’, about the colonized people in history, to correct the western misconception and misinterpretations about the colonized people elsewhere. It is the right way to rewrite colonized history, western cultural hegemony, and present reality about any native people and culture based on established critical modalities so far.